MATERNAL PSYCHOLOGICAL CHANGES DURING PREGNANCY AND PREGNANCY SERVICE PROCEDURES DURING THE COVID-19 PANDEMIC IN KERTOSARI VILLAGE - Miftahul Hakiki; Nurul Eko Widiyastuti (Journal of Health Community Service, 2021)
In general, a mother who is experiencing pregnancy for the first time will feel happy and will be more curious about self-change and fetal development. However, at the same time, pregnant women also feel anxious. Research conducted in Naples, Italy, March 15-April 1, 2020, shows that the Covid-19 pandemic has a severe psychological impact on 53% of pregnant women. During pregnancy, women may experience stress and anxiety, this can cause detrimental effects such as fetal death or fetal abnormalities. Antenatal Care is a pregnancy check that aims to improve the physical and mental health of pregnant women optimally so that they are able to face childbirth, childbirth, preparation for exclusive breastfeeding, and the return to reproductive health properly. The solution to this community service is to provide counselling about psychological changes in pregnant women and how to get pregnancy services during the Covid-19 pandemic, which in fact has changed a lot compared to before the Covid-10 pandemic, so it is hoped that it can reduce the anxiety faced by mothers during this period. pregnancy and still want to carry out pregnancy checks at a health worker or midwife accompanied by a health cadre, during which during the Covid-19 pandemic, pregnant women continue to carry out their pregnancy checks according to the minimum standard, which is 4 times during pregnancy. The implementation of this counselling activity is carried out for pregnant women and health cadres in Kertosari Village in a gradual period of time and does not leave the health protocol determined by the Government. The results obtained are the enthusiasm of pregnant women and health cadres who will accompany them during the process of pregnancy examinations.